La gestión del docente frente a la problemática de la deserción de los estudiantes, de la Unidad Educativa Intercultural Bilingüe “Jatari Unancha” de la parroquia Zumbahua del cantón Pujilí - Basantes Bastidas, Byron Esteban (2016)
Research can learn about the dropout students Intercultural Bilingual Education Unit "Jatari Unancha" and teaching management in this unit is made according to existing problems. The analysis on the teaching management against dropouts detected in the educational establishment. To avoid dropout is generated in the student's desire to study in the search for personal improvement and see the study as a means of self-improvement and therefore acceptance in a society that works allocating work roles to qualified people to meet them the factors are many pear teacher management to seek the necessary means to educate their work is completed satisfactorily alternatives….